Nasolabial Flap and Simultaneous Cartilage Graft for Nasal Alar Reconstruction- A Case Report - Moniruzzamzn, MM; Sarker, Avijit; Harun, Md Abdullah Al; Islam, Iftekharul; Sabuj, Mujahidul Islam (Bangladesh Journal of Otorhinolaryngology, 2021)
A case of full thickness defect involving left ala of nose reconstructed with nasolabial flap for the coverage of skin and mucosal lining, along with simultaneous insertion of septal cartilage, which completes the reconstruction. Bangladesh J Otorhinolaryngol 2021; 27(2): 184-187